Mental Process in Milk and Honey Poems Collection by Rupi Kaur - Nuning Yudhi Prasetyani; Tiara Nugi Fitriafi; Maisarah Maisarah (Merwinspy Publisher, 2023)
This study applies one of the scopes of SFL in Milk and Honey poems collection. This study examines the mental process in Milk and Honey poems collection. The purposes of this study are (1) to identify the kinds of mental processes in Milk and Honey poems collection, (2) to explain the reason of the author represented the kinds of mental processes in Milk and Honey poems collection. By using a descriptive method, this research tries to describe the facts concerning the objects of the research, namely mental process. Therefore, the researcher collects the data, analyzes, and derives conclusions about the various forms of mental process in Milk and Honey poems collection and the way the author represents the form of mental process in Milk and Honey poems collection. This study uses theory from Halliday & Matthiessen. According to the theory, the mental process is divided into three types: cognition, affection, and perception. The analysis shows that cognition and perception dominates the author’s representation in Milk and Honey poems collection, while affection is the least type that appears in this poems collection. Those are implied that the author wants to tell women for using their thought and sensitivity instead of using their feeling to express their supposed intention.